2023
DOI: 10.1007/s00271-023-00855-w
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative response of Tempranillo vines to the crop forcing technique and pre-forcing and post-veraison water stress in terms of yield and grape and wine quality

Abstract: Elevated temperatures during berry ripening are detrimental to grape quality. The crop forcing technique (summer pruning that ‘forces’ the vine to start a new cycle) increases must acidity and malic acid concentration at harvest by delaying the date of veraison. However, little information is available on the sensitivity to water stress of forced vines. A 3-year trial was conducted to test three irrigation strategies in forced vines: a minimum threshold of mid-day stem water potential (Ψs) of −0.75 MPa before … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 46 publications
5
13
1
Order By: Relevance
“…The later grape ripening confirmed that the temperature and humidity conditions in September and October were more favorable for a balanced grape composition. Thus, double pruning did increase the TA in relation to TSSs, and the tartaric-to-malic acid ratio in relation to TSSs, as other authors reported in other cultivars ( Gu et al., 2012 ; Martínez de Toda et al., 2019 ; Martínez-Moreno et al., 2019 ; Oliver-Manera et al., 2023 ). These increases can be beneficial for wine stability as higher titratable acidity and a low tartaric-to-malic acid ratio decrease must pH.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The later grape ripening confirmed that the temperature and humidity conditions in September and October were more favorable for a balanced grape composition. Thus, double pruning did increase the TA in relation to TSSs, and the tartaric-to-malic acid ratio in relation to TSSs, as other authors reported in other cultivars ( Gu et al., 2012 ; Martínez de Toda et al., 2019 ; Martínez-Moreno et al., 2019 ; Oliver-Manera et al., 2023 ). These increases can be beneficial for wine stability as higher titratable acidity and a low tartaric-to-malic acid ratio decrease must pH.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, given the large delay in the phenology caused by double pruning, the periods of maximum evapotranspirative demand occurred in different phenological stages than in the control or shaded vines. This may increase water requirements in forced vines as compared to the control, as Oliver-Manera et al. (2023) recently observed.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The effects of surface water irrigation shortages attributable to climate change are smaller than the direct biophysical impacts of climate change on yield on the national level. Anderson et al [52] indicated that the vines in Oliver-Manera et al [53] and olives in Ahumada-Orellana et al [54] showed great sensitivity to deficit irrigation in their yields, in their review paper.…”
Section: Water Supply and Irrigationmentioning
confidence: 99%
“…The crop forcing technique (also known as the forcing regrowth technique) has become a topic of research interest since it has proven to be a useful technique to delay the harvest date by as much as two months [3]. As a result, the berries ripen under cooler conditions with an increase in must acidity and malic acid concentration [3][4][5][6][7]. However, vines in which the crop forcing technique is carried out have a reduced yield [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%